The gender variance scale: developing and piloting a new tool for measuring gender diversity in survey research. - Yarrow, Elizabeth; Duschinsky, Robbie; Saunders, Catherine L (Journal of Gender Studies, 2024)
This paper discusses the development and testing of a new composite scale for measuring gender diversity, for use in survey research and statistical analysis: the Gender Variance Scale (GVS). The GVS measures gender diversity on a spectrum and can be used across both cisgender and trans populations to identify experiences of gender beyond a basic male/female sex binary. The GVS was piloted with a sample of 1,776 adolescents and young people ages 14–24 years, in the context of a broader study exploring the relationships between gender variance, young people's experiences and wellbeing. Analysis of data indicated that the GVS contained both face and construct validity and reliability in the context of the pilot study. In addition, the data revealed some interesting associations between the GVS and other demographic features of the sample of youth surveyed; for example, higher levels of gender variance were associated with being lesbian, gay or bisexual and having a disability. The findings of this study may be of interest for building a stronger empirical understanding of gender diversity and its intersections with other aspects of identity.